Development of technological competencies: a precondition for life long learning - Sederevičiūtė - Pačiauskienė, Živilė; Miškinienė, Manefa; Norkienė, Eurika (Pedagogika, 2014)
Relevance. The rapid growth of technological progress has necessitated a need for adult lifelong learning and acquisition of knowledge and skills in new fields, as well as increased the importance of technological competencies in the context of lifelong learning, therefore, this thesis is of particular relevance in the light of current developments. The problem of the study: though the emphasis on the continuous learning has been increasing, the development of lifelong learning skills through technologies has been short of proper attention and thus under-examined. The focus of the study: the development of technological competencies in the context of lifelong learning. The subject of the study:Lithuanian adult population aged from (18 to 60 or more). The purpose of the study:to explore the development of technological competencies as a precondition for lifelong learning.Objectives: 1) to determine needs, factors and techniques for lifelong learning, 2) to find out adults’ learning interests as regards technologies, 3) to find out the reasons and obstacles in the context of lifelong learning, 4) based on the outcomes of the study, to determine respondents’ approach to the development of technological competencies for lifelong learning. The study was carried out in 2013. The subject groupcomprised adult Lithuanian respondents above 18 years of age. The study methods:analysis of scholarly literature and documents; empirical research – a survey (250) and structured interviews (5) mathematical analysis of data. The analysis of the study outcomes showed that the main lifelong learning needs are basically associated with the desire to gain knowledge and skills that had failed for certain reasons in the past. What plays an important role in continuous learning of the subjects is internal factors, such as the desire to gain knowledge, to excel, as well as other needs and interests. It was found that adults prefer learning spontaneously, i.e. through their own experience, interactions with colleagues, friends. The analysis of technology interests in adults have revealed that most competencies are acquired in the field of nutrition while cooking Lithuanian or other national dishes, also in creating design for objects and the environment, organizing trips, and creating home interior or exterior design. The study has also shown that women tend to develop their competencies in textiles and floristic field, while men – in construction materials and products. The study has found that the desire to learn more about new technologies and the desire to improve the quality of life is driven strongest by inner motives, leading to continuous technological development. The most common reasons keeping people from learning are external: lack of money, difficulties in matching learning with work and family duties. Despite the variety of learning obstacles, the majority of the respondents were for the continuous technology learning. This shows that the technological competencies development is a precondition for lifelong learning.